Resilience and Moral Character Among University Students in the Era of Technological Disruption: A Phenomenological Study of BKI Students at UIN Mataram - Fitriana, Herlina; Prayona, Baiq Arwindy; Bafadal, Iqbal (KOMUNITAS, 2025)
Based on preliminary research findings, many students feel easily defeated by their circumstances and tend to complain. Additionally, many students experience a degradation in morality when communicating with lecturers. The method used in this study is qualitative with a phenomenological approach, interviewing 20 students from the BKI program. The results show that only 5 out of 20 students are resilient, while the other 15 tend to give up easily and experience stress, with 2 of them even contemplating suicide. Based on the interviews, it was found that each student is capable of both good and bad behaviors, such as stealing, lying, showing a lack of empathy, and being impolite toward elders. Their moral character varies, influenced by personal experiences, trauma, and their environmental conditions.